Pharmacokinetics of halofantrine in man: effects of food and dose size. - Milton, K A (1989)
1. Plasma concentrations of halofantrine (Hf) and its putative principal plasma metabolite desbutyl halofantrine (Hfm) have been measured in two separate studies after oral administration of the hydrochloride salt. 2. Six healthy male volunteers each received single oral doses of 250, 500 and 1000 mg administered after an overnight fast. A washout period of at least 6 weeks was allowed between each dose. A further 250 mg single oral dose was administered to the same six subjects in a fasting state and after a standardised fatty meal in a randomised study, again with a washout period of at least 6 weeks. 3. AUC and maximum plasma concentration (Cmax) for Hf increased in proportion to the dose from 250-500 mg. This increase was non-proportional when the dose was increased from 500 to 1000 mg. For Hfm, in the dose range 250-500 mg, AUC but not Cmax increased in proportion in the increase in dose size. The increase in these parameters was non-proportional when the dose was increased from 500 to 1000 mg. Time to reach peak concentrations for Hf and Hfm and the elimination half-life of Hf remained unchanged across the dosage range. 4. Following a fatty meal, Cmax for Hf was increased from 184 +/- 115 micrograms l-1 (fasting) to 1218 +/- 464 micrograms l-1 (fed). AUC for Hf was increased from 3.9 +/- 2.6 mg l-1 h (fasting) to 11.3 +/- 3.5 mg l-1 h following a fatty meal.(ABSTRACT TRUNCATED AT 250 WORDS)